Mpeg-Dash System via HTTP2 Protocol with HEVC Encoder for Video Streaming Services - Dr.N.Nafea Kamiss, E.Mustafa Muhammed Awad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
MPEG-DASH is an adaptive bitrate streaming technology that divides video content into small HTTP-objects file segments with different bitrates. With live UHD video streaming latency is the most important problem. In this paper, creating a low-delay streaming system using HTTP 2.0. Based on the network condition the proposed system adaptively determine the bitrate of segments. The video is coded using a layered H.265/HEVC compression standard, then is tested to investigate the relationship between video quality and bitrate for various HEVC parameters and video motion at each layer/resolution. The system architecture includes encoder/decoder configurations and how to embedded the adaptive video streaming. The encoder includes compression besides adaptive streaming, while decoder includes displaying of compressed video and the function of network sensing. The videos streaming is tested over two IP networks, Unicast and Multicast. A maps of network performance evaluation and how influences of different videos is achieved through sensors installed at main network nodes.